Teacher Training to Handle Bullying in the School in Indonesia - Hidayatus Sholihah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
There are several students in Indonesia who have suffered from injury or even died because of bullying. As a consequence, school teachers in Indonesia need to be trained to handle and prevent bullying. This essay examines the importance of pre-service and in service teacher training in order to reduce and prevent bullying in school in Indonesia by examining the problem of bullying, discussing the effects of it and providing areas of training to help teachers to tackle bullying. There are several reasons why bullying becomes serious problem in school. First of all, bullying is a complex task for teachers because it is difficult to identify and, teachers find it difficult to differentiate between bullying and fighting or horseplay. Moreover, teachers lack the knowledge and skills to handle bullying. Bullying has negative effects not only on victims but also on bullies. Victims feel lonely, depressed, and often have low self-esteem, while bullies often exhibit sign of bad temper or depression. Areas of teachers pre- service and in- service training are1) assisting teachers to differentiate between bullying and fighting or horse playing 2) developing skills to communicate with bullies and to manage classrooms where bullying occurs. In conclusion, teacher training is a good solution to tackle bullying at school in Indonesia because teachers are in the front line to solve this problem. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1786